Snowbound - Martin, Ann M., 1955- (New York : Scholastic, 1991)
When the snow finally comes to Stoneybrook, no one is prepared for the storm that hits. Some of the babysitters are stranded and snowed in, and Stacey is in real trouble.
"An Apple paperback.".
5.1
3-6
Keywords: Babysitters -- Fiction; Blizzards -- Fiction; Babysitters -- Fiction; Blizzards -- Fiction